2020
DOI: 10.1007/s00404-020-05563-w
|View full text |Cite
|
Sign up to set email alerts
|

Motherhood after cancer: fertility and utilisation of fertility-preservation methods

Abstract: Purpose Due to modern and individualised treatments, women at reproductive age have a high survival rate after cancer therapy. What are pregnancy and birth rates of women after cancer and how often do they use cryopreserved ovarian tissue or gametes? Methods From 2007 to 2015, 162 women aged 26.7 ± 6.9 years were counselled for fertility preservation at a single University Fertility Centre. A questionnaire study was performed in average 3 and 6 years after the diagnosis of cancer. The women were asked about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
0
10
0
2
Order By: Relevance
“…increasing survival rates in female cancer survivors of reproductive age have led to the development and increased use of several fertility preservation techniques [2]. However, fertility preservation procedures are usually expensive and time-consuming [24].…”
Section: Fertility Preservation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…increasing survival rates in female cancer survivors of reproductive age have led to the development and increased use of several fertility preservation techniques [2]. However, fertility preservation procedures are usually expensive and time-consuming [24].…”
Section: Fertility Preservation Methodsmentioning
confidence: 99%
“…in developing countries, over the last decades, cancer is increasingly common in women of childbearing age [1,2]. Breast cancer, cervical cancer, thyroid cancer, non-Hodgkin's lymphoma, and leukemia are the most frequent cancers among women younger than 40 [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, these women should not be discouraged from becoming pregnant. A recent study by Poorvu PD et al [16] demonstrated that many women remain interested in future fertility in the 4 years after a breast cancer diagnosis but only a minority of them attempt to become pregnant and another study reported that 51% of cancer survivors who underwent fertility preservation had a strong wish to conceive about 3 years after treatment but only 29% had tried to conceive [111] and two different studies reported a utilization rate of cryopreserved embryos or oocytes of 8-29% [112] and of 24% [113]. Young cancer survivors may face several barriers to safely and successfully conceiving a pregnancy [22] but a multidisciplinary team should counsel women in the best way to give them adequate information to make conscious choices, knowing the real risks and removing the shadows of fears about what is safe.…”
Section: Pregnancies In Cancer Patientsmentioning
confidence: 99%
“…Therefore, no spontaneous menstruation within a year is frequently associated with permanent ovarian damage and induced menopause [39]. All patients with gonadotoxic therapy for cancer, with temporary ovarian damage, experience premature menopause [96]. The difference depends on the number of remaining primordial follicles.…”
Section: Fertility Preservation After Cancer Treatmentmentioning
confidence: 99%